(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: How diverse are thermophilous forest edge communities on the Southern Podolia? Location: National Nature Park “Karmeliukove Podillia”, Vinnytsia Region, Ukraine. Methods: A short data set of 27 recent and 2 historical vegetation plots is used for this study. Phytosociologial relevés were stored in the database created by Turboveg softwear and analyzed using modified TWINSPAN algorithm within JUICE 7.1 softwear. Ecological conditions were estimated using Ellenberg Indicator Values. Nomenclature: Euro+Med PlantBase https://europlusmed.org, Mucina et al. 2016 Results. For the study area, 3 associations and 2 communities from the class Trifolio-Geranietea sanguinei are distinguished. In landscape, they differ according to the position regarding on surrounding vegetation types rather than environmental gradient. Narrow strips formed by Lathyrus niger and Vicia pisiformis along linear inner edges in open oak forests we attribute to the alliance Knaution dipsacifoliae. Mesophilous semi-shade communities dominated by Agrimonia procera on the egdes of oak-hornbeam forests on gray loamy soils belong to the alliance Trifolion medii. Position of plant community with Campanula cervicaria remains uncertain even though it has been identified previously to the association level. Thermoxerophilous communities with Peucedanum alsaticum on chornozem soils in peripheral zones of shrub vegetation surrounded by meadow steppe on gentle slopes represent the aliance Geranion sanguinei. The association Trifolio alpestris- Melampyretum cristati is known on historical data only. Four of communities determined on this study are mentioned for the first time for Ukraine. Conclusions. South Podolian Forest-Steppe supports significant diversity of the thermophilous forest edges and glades. Historical (ca. 100 years old) geobotanical data could be still useful as an additional source for phytosociological survey if even incomparable in terms of plot area and species number. Considerable shift of the eastern limit range for the alliance Knaution dipsacifoliae is proposed based on obtained materials.